Statistical inference based on the likelihood - Azzalini Adelchi (Boca Raton Chapman & Hall, 2002)
This book introduces likelihood-based statistical theory and related methods from a classical viewpoint, and demonstrates how the main body of currently used statistical techniques can be generated from a few key concepts, in particular the likelihood.
Keywords: Statistical inference